Simultaneous Seebeck coefficient and electrical conductivity enhancement of GeSbTe films via Sn addition - Khwansungnoen, Phalakorn; Daichakomphu, Noppanut; Sukwisute, Pisan; Limsuwan, Pichet; Somdock, Nuttakrit; Harnwunggmoung, Adul; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn (My University, 2022)
Sn-added GeSbTe (GST) thin films were deposited using a co-magnetron sputtering technique. The effects of varying the Sn content through a variable Sn target sputtering power and post annealing at 673 K were investigated. The DC power density applied to the GST target was controlled at 50 W, while the power density of the Sn target was increased from 0 W to 40 W. The results demonstrate the coexistence of the fcc-GST, hcp-GST and SnTe phases in the Sn-added GST thin films. The substitution of Sn at the Ge-site increases the crystallization speed and leads to defects and lattice disordered local arrangement in the GST films, causing the Seebeck coefficient to increase. The SnTe phase was created as a result of the high Sn content in the sample due to the over-doping limit of Sn into the GST structure. The presence of SnTe in Sn-doped GST films increased the electrical conductivity. The maximum power factor of 17.0 μW/cmK2 at 450 K was obtained at an Sn content of 14.7 at%. These results indicated that the thermoelectric properties of Sn-doped GST films were improved via the formation of an appropriate amount of SnTe composite.
Keywords: GST film; Magnetron sputtering; Sn doped; SnTe; Thermoelectric properties